Biomimetic Prosthetics - Vinjamuri, Ramana (IntechOpen, 2018)
Biomimetic prosthetics are advanced devices that mimic the physical and functional properties of the replaced limb, thus restoring near-natural form and function. This flourishing field of research will continue to play an important role in improving quality of life, independence, and community participation for individuals with disabilities. This humble compilation showcases a few representative examples of progress in this exciting field.